A New Most Beautiful Name of Allāh in an Early Islamic Inscription from Southern Jordan? - al-Ghul, Omar (Jordan Journal for History and Archaeology, 2023)
This study tackles a personal name that appears in an Arabic inscription from the early 2nd century of the Islamic era that W.J. Jobling discovered in Wādī Shīrah in southern Jordan in the 1980s . Although several authors dealt with the inscription, they did not pay enough attention to the name of the inscription’s owner that appears in line four as ʽbd l-ʽlā. After discussing the possible vocalizations of the name, the paper comes to favor the form ʽAbd al-ʽAlā and it draws the attention to the fact that it appears for the first time in the Arab onomastics. More importantly, the study points out that this name contains a so far unattested epithet of Allāh. Thus, the paper offers a brief review of the “The Most Beautiful Names of Allāh” and their canonization and considers the circumstances that allowed for coining this new “Beautiful Name”. It concluded that this was made possible, firstly because of the liberal theological stance towards the corpus of “The Most Beautiful Names of Allāh”, which regarded it as an open list of epithets, and secondly based on the name’s affinity to the other “Beautiful Names” derived from the verb ʽalā.